2021
DOI: 10.1002/jcla.23885
|View full text |Cite
|
Sign up to set email alerts
|

Novel mortality‐predicting index at diagnosis can effectively predict all‐cause mortality in patients with antineutrophil cytoplasmic antibody‐associated vasculitis

Abstract: Background This study investigated whether the inflammation prognostic index (IPI) and the mortality predicting index (MPI) at diagnosis could predict all‐cause mortality in patients with antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV). Methods We included 223 AAV patients and reviewed their medical records. Clinical and laboratory data and AAV‐specific indices at diagnosis were assessed. The IPI was calculated as neutrophil‐to‐lymphocyte ratio (NLR) × C‐reactive protein to albumin ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We also previously reported that 1-, 5-, and 10-year cumulative patient survival rates of 96.1, 94.8, and 92.8%, respectively, in Korean patients with AAV ( 8 ). Therefore, it is believed that in addition to accurate early diagnosis and early treatment initiation, the efforts to discover new indices to predict poor outcomes, particularly all-cause mortality may improve the prognosis of AAV ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also previously reported that 1-, 5-, and 10-year cumulative patient survival rates of 96.1, 94.8, and 92.8%, respectively, in Korean patients with AAV ( 8 ). Therefore, it is believed that in addition to accurate early diagnosis and early treatment initiation, the efforts to discover new indices to predict poor outcomes, particularly all-cause mortality may improve the prognosis of AAV ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%